Taxman's Dilemma: Coercion or Persuasion? Evidence from a Randomized Field Experiment in Ethiopia - Shimeles, Abebe; Gurara, Daniel Zerfu; Woldeyes, Firew (American Economic Review, 2017)
We analyze data from a randomized controlled trial of two innovative anti-tax evasion schemes in Ethiopia that signal threats of audit and complimentary messages that encourage tax morale. Our results indicate that the threat of audit reduces tax evasion significantly, and its effect is higher in businesses commonly suspected of high tax evasion rates. We also find that appealing to the tax morale promotes compliance but slightly less than that of audit threat. Our results are robust to different estimation strategies and less sensitive to potential confounding factors.